Construire des outils d'évaluation de l'efficacité d'un dispositif pédagogique à distance : le cas de l'efficacité interne d'IFADEM RDC/Katanga. - Charlotte Pourcelot; Sandoss Ben Abid-Zarrouk (Centre National d'Enseignement à Distance, 2015)
Evaluating the efficiency of a teacher training system requires to define it and to use an assessment grid adapted to the situation in which it is applied. Through the study of distance teaching (IFADEM) aimed at teachers from French-speaking countries in the south, we intend to show how the institutional means of evaluating this distance teaching in the case of the teachers of the RDC Katanga, allow the evaluation of the efficiency of this way of teaching. At the end of the IFADEM training sessions, teachers were more likely to respond positively to the questions in the training booklets. The qualitative survey could not be exploited because the samples were not comparable. This research has shown that the assessment tools have only partly been able to prove the effectiveness of this distance learning environment.